Establishing Pollution Levels and Monitoring Air Quality in Eastern Indonesian Mining Areas - Nur Aini Fauziyah; Billy Sopater Maniani; Reffany Choiru Rizkiarna; Fajar Timur; Arum Sinda Santika (Nusantara Science and Technology Proceedings, 2024)
This study aims to measure pollution levels and track the state of the air in Eastern Indonesia's major mining districts. Eastern Indonesia's mining in-dustry has significantly boosted the local economy in the area. But this also brings up environmental issues, particularly with relation to pollution and air quality. The level of sulfur dioxide (SO2), nitrogen dioxide (NO2), and other pollutants is measured using the EPM-Manual 42iQ Continuous Air Quality monitoring tool in this air quality inspection method. Our research reveals higher than expected pollution levels around mining activities, sur-passing both national and international air quality regulations. The study also shows that pollution concentrations vary seasonally, with higher levels during the dry season. Furthermore, health risk assessments show possible negative effects on locals.